Modelling of pedestrian level wind environment on a high-quality mesh: A case study for the HKPolyU campus. (May 2018) - Du, Yaxing; Mak, Cheuk Ming; Ai, Zhengtao
Abstract: Quality and efficiency of computational fluid dynamics (CFD) simulation of pedestrian level wind environment in a complex urban area are often compromised by many influencing factors, particularly mesh quality. This paper first proposes a systematic and efficient mesh generation method and then performs detailed sensitivity analysis of some important computational parameters. The geometrically complex Hong Kong Polytechnic University (HKPolyU) campus is taken as a case study. Based on the high-quality mesh system, the influences of three important computational parameters, namely, turbulence model, near-wall mesh density and computational domain size, on the CFD predicted results of pedestrian level wind environment are quantitatively evaluated. Validation of CFD models is conducted against wind tunnel experimental data, where a good agreement is achieved. It is found that the proposed mesh generation method can effectively provide a high-quality and high-resolution structural grid for CFD simulation of wind environment in a complex urban area. Highlights: An efficient and systematic mesh generation method is proposed. The sensitivity analyses of some important computational parameters are conducted. The pedestrian level wind environment of HKPolyU campus is accurately predicted. The findings can provide supplemental information for modelling complex urban area.